A Two-Scale Asymptotic Analysis of a Time-Harmonic Scattering Problem with a Multi Layered Thin Periodic Domain (Communications in Computational Physics, 2009)
The scope of this paper is to show how a two-scale asymptotic analysis,based on a superposition principle, allows us to derive high order approximate boundaryconditions for a scattering problem of a time-harmonic wave by a thin and tangentiallyperiodic multi-layered domain. The periods are assumed of the same order of thethickness. New terms like memory effect and variance-covariance ones are observedcontrarily to the laminar case. As a result, optimal error estimates are obtained.